Psychiatric morbidity and substance use in migrant workers: A population based study. (February 2022) - Chavan, B.S.; Sidana, Ajeet; Arun, Priti; Rohilla, Ravi; Singh, Gurvinder Pal; Solanki, R.K.; Aneja, Jitender; Murara, Mankirat Kaur; Verma, Madhur; Chakraborty, Saikat; Singh, Chitra; Sharrma, Himanshu; et al.
Background: The prevalence of mental health problems and substance abuse in the migrant population is higher than the general population. Aims and Objectives: To assess the prevalence and pattern of mental health issues and substance use in the migrant population and highlight the association with the reverse migration of migrant workers. Methodology: The field staff visited the shelter homes for migrant population in four cities of Northern India (Chandigarh (UT), Bhatinda (Punjab), Panchkula (Haryana) and Jaipur (Rajasthan). After maintaining the social distance and wearing masks by the staff and migrants, written informed consent was taken for participation in the study. The socio-demographic details of reverse migrants were noted down and Hindi version of Patient Health Questionnaire (PHQ-9) for mental health problems and screening tool for pattern of substance abuse was administered. Geographically matched undisplaced were also administered these tools. Results: A total of 275 reverse migrants and 276 undisplaced were included in the study. The prevalence of ever use for all the substances among reverse migrants was 44.4% (122/275) and among undisplaced, it was 45.3%. The prevalence of alcohol, tobacco and cannabis was higher than the general population. The prevalence of at least one diagnosis on PHQ-9 is 13.45% (reverse migrants 19.3% and undisplaced 7.6) and the prevalence of other depressive disorder is significantly higher in reverse migrants (17.1%) than undisplaced (4.0%). Conclusion: The study concludes that prevalence of mental health issues and substance abuse in migrant population is significantly higher than the general population and the prevalence of at least one diagnosis and other depressive disorder is significantly higher in reverse migrants than undisplaced.